News reporting and writing - Mencher, Melvin (Boston: Mc Graw - Hill Higher Education, 2000)
Contents: part one: the reporter at work - 1. one the job. part two: the basics - 2. components of the story. part 3: writing the story. - 3. what is news? 4. the tools of the trade. 5. story structure. 6. the lead. 7. the writer's art. 8. features, long stories and series. 9. broadcast newswriting. part four: reporting principles. 10. digging for information. 11. making sound observations. 12. building and using background. 13. finding, cultivating and using sources. part five: from accidents to education. part six: laws, taste and taboos, codes, and ethics.
Glossary p. 766 - 773 name index p. 774 - 787 subject index p. 788 - 794. es acompañado con un manual para el instructor. ver inv 2351 y un workbook, ver inv. 2352
Keywords: Reportes and Reporting - Journalism